IgG4-Related Disease in a Urachal Tumor - Travis W. Dum; Da Zhang; Eugene K. Lee (Case Reports in Urology)
IgG4-related disease is a newly recognized fibroinflammatory disorder that has the ability to affect nearly every organ system. It is characterized by tumefactive lesions and fibrosis and closely mimics neoplasms. Only one case of IgG4-related bladder mass has been reported in the literature, but there are no reports of IgG4-related disease in a urachal mass. Herein, we report a 26-year-old male who initially presented with symptoms of recurrent UTI. Work-up revealed a 6 cm urachal tumor, a 1.4 cm pulmonary lesion, and mediastinal lymphadenopathy; all metabolically active on PET scan and suspicious for urachal adenocarcinoma. Lung lesion fine needle aspiration and TURBT pathology revealed inflammation but no evidence of malignancy. The patient underwent a partial cystectomy and umbilectomy with pathology demonstrating dense plasmacytic cells, a high rate of immunohistochemistry staining positive for IgG4 plasma cells, a storiform pattern of fibrosis, and an obliterative phlebitis. Furthermore, the patient had an elevated serum IgG4 level of 227 mg/dL (range 2.4–121 mg/dL). IgG4-related disease is a newly recognized fibroinflammatory disorder that can mimic neoplastic processes and a high index of suspicion and accurate tissue pathology is necessary for an accurate diagnosis.